σ-Stabilization of a Flexible Joint Robotic Arm via Delayed Controllers - G. Ochoa-Ortega; R. Villafuerte-Segura; M. Ramírez-Neria; L. Vite-Hernández (Complexity)
In the present contribution, the problem of establishing tuning rules to proportional retarded controller for LTI systems is addressed. Based on the D-decomposition methodology and σ-stability analysis, analytic conditions are determined on the parameters of a delayed controller that guarantee us that the system response reaches the maximal decay rate. The conditions presented in this paper are tested experimentally in tracking tasks of a flexible joint robotic arm.